Multiple accounting and driving factors of water resources use: A case study of Shanghai. (1st July 2022) - Pan, Ting; Fan, Yiyuan; Shao, Ling; Chen, Bin; Chu, Yuwen; He, Guojia; Pan, Yunlong; Wang, Wenqing; Wu, Zi
Abstract: Previous research papers on urban water resources accounting were confined to the perspectives of production and consumption, ignoring the perspective of income. This paper proposes a systems framework to analyze the income, production, and consumption-based water uses and underlying driving forces of a city based on the methods of multi-scale input-output analysis and structural decomposition analysis. A case study is performed for Shanghai as a megacity. The results show that the income, production and consumption-based water uses of Shanghai had decreased from 5.70 billion m 3, 10.85 billion m 3 and 28.45 billion m 3 in 2007 to 2.80 billion m 3, 6.20 billion m 3 and 24.10 billion m 3 in 2017, respectively. Domestic imported primary inputs had emerged as an important virtual water supplier of Shanghai and its share of total supply-side water use had increased from 23.92% in 2007 to 42.95% in 2017. Meanwhile, about 46% and 40% of Shanghai's total consumption-based water use had been imported from other Chinese regions and foreign countries in 2017, respectively. It is revealed that trade played an important role in relieving water use pressure in Shanghai. The factors that had increased the uses of water resources in Shanghai include population, per capita value-added, per capita output, final consumption structure, and per capita final consumption. The factors that had reduced the water uses in Shanghai include technology, value added mix, output structure, value added structure, domestic import, commodity mix, and foreign import. It is suggested that in addition to curbing urban water use from the production side, more targeted water-saving measures should be devised from the supply (e.g., restricting loan to heavy water-consuming enterprises) and consumption sides (e.g., encouraging residents to buy low-water products). Highlights: A framework to quantify the income, production, and consumption-based water uses. Analyzing the socioeconomic driving forces of urban water uses comprehensively. All three kinds of Shanghai's water uses had decreased during 2007–2017. Imported primary inputs and products are significant to Shanghai's water uses. Targeted suggestions from supply, production, and demand sides are proposed.